Analysis of facilities and infrastructure on improving the achievement of jepara district athletes - Nur Asiyah; Nanang Indardi (Media Ilmu Keolahragaan Indonesia, 2025)
This study aims to analyze the role of sports facilities and infrastructure in supporting the achievement development of pencak silat athletes in IPSI Jepara Regency. The research is grounded in the premise that adequate training facilities are crucial for effective coaching, athlete motivation, and performance outcomes. A qualitative approach was applied, employing in-depth interviews and participatory observations. Participants consisted of 5 athletes (3 male, 2 female), 3 coaches, and 2 IPSI administrators. Data were analyzed through reduction, display, and conclusion drawing. The findings reveal that the availability of facilities and infrastructure remains limited in both quantity and quality, affecting training effectiveness, athlete comfort, and self-confidence in competitions. Nevertheless, athletes and coaches maintain strong motivation despite the minimal training environment. The study concludes that improving the quality and availability of sports facilities is essential to enhance pencak silat performance at regional and national levels